2022
DOI: 10.1021/acsnano.2c00266
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Nanocrystals of Small Molecules and Chemically Disordered Polymers

Abstract: Organic crystals formed by small molecules can be highly functional but are often brittle or insoluble structures with limited possibilities for use or processing from a liquid phase. A possible solution is the nanoscale integration of polymers into organic crystals without sacrificing long-range order and therefore function. This enables the organic crystals to benefit from the advantageous mechanical and chemical properties of the polymeric component. We report here on a strategy in which small molecules coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…160,161 The band structure could be tuned through chromophore co-assembling and alloying between crystalline aggregates, 162,163 as well as attaining precise integration of the catalytic components (already demonstrated with covalent polymers). 164 Improving the mechanical (and photophysical) properties of self-assembled chromophores, which could be achieved with hybrid supramolecular covalent materials, [165][166][167] could allow the preparation of robust photocatalysts that might be even 3D printed. 168 Finally, the dynamic nature of the aggregates could be used to obtain photocatalytic activity in an out-of-equilibrium state.…”
Section: Discussionmentioning
confidence: 99%
“…160,161 The band structure could be tuned through chromophore co-assembling and alloying between crystalline aggregates, 162,163 as well as attaining precise integration of the catalytic components (already demonstrated with covalent polymers). 164 Improving the mechanical (and photophysical) properties of self-assembled chromophores, which could be achieved with hybrid supramolecular covalent materials, [165][166][167] could allow the preparation of robust photocatalysts that might be even 3D printed. 168 Finally, the dynamic nature of the aggregates could be used to obtain photocatalytic activity in an out-of-equilibrium state.…”
Section: Discussionmentioning
confidence: 99%
“…Such systems could perform valuable functions with low energy inputs across different spatial scales. In our work investigating hybrid bonding materials, 19,20 which chemically integrate supramolecular polymers and covalent polymers, we have observed enhancement of such functions as a result of dynamic phenomena linked to supramolecular polymers. Specifically, we have observed that forms of these materials responsive to external light as a result of their spiropyran moieties present in their covalent component exhibit faster bending actuation when supramolecular polymers are chemically integrated in their microstructure (Figure 5).…”
Section: Supramolecular Motion and Functionmentioning
confidence: 97%
“…The extra-large 2D nanosheets created loosely packed hydrogel scaffolds that greatly enhanced photocatalytic H 2 production with TON as high as 13 500 over ∼110 h (table 1, entry 21). Recently, they further reported a cocrystallization strategy of small molecules and chemically disordered polymers to create hybrid nanosheets and nanofibers containing a highly ordered lattice and studied their photocatalytic HER performance [88].…”
Section: Nanosheets For H 2 Productionmentioning
confidence: 99%